Glucagon-Like Peptide-1 Receptor Agonists in Cognitive and Mental Health Disorders: A Comprehensive Review of Pre-Clinical and Clinical Evidence - Ana Ghenciulescu; Riccardo De Giorgi; Oliwia Dziwisz; Catherine Harmer (BJPsych Open)
Aims: Glucagon-like peptide-1 receptor agonists (GLP-1RAs) such as semaglutide are considered breakthrough drugs in the management of diabetes and obesity. Beyond their metabolic benefits, these pharmacological agents interact with biological pathways that may influence brain function, and are therefore increasingly being investigated for possible repurposing in psychiatric and neurological disorders. This review aims to synthesise pre-clinical and clinical evidence on the effects of GLP-1RAs across a range of cognitive and mental health conditions, comprehensively assessing their therapeutic potential and translational implications for psychiatric practice.